2007
DOI: 10.1007/s00467-006-0306-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustained beneficial effect of intravenous bisphosphonates after their discontinuation in children

Abstract: We studied if the beneficial effects of bisphosphonates are maintained after their discontinuation, and whether adverse effects may develop. Seventeen children in whom I.V. bisphosphonates were discontinued for at least 12 months were included. Fracture rate (FR), skeletal pain, bone mineral density of total body (TB) and spine L(2-4), skeletal radiographs, bone markers and kidney functions were compared between: (a) before treatment, (b) end of treatment, and (c) last follow-up. Mean treatment duration was 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Some studies have reported a trend toward an increase of height in children treated with intravenous bisphosphonates compared with pretreatment values [61,62].…”
Section: Biphosphonatesmentioning
confidence: 95%
“…Some studies have reported a trend toward an increase of height in children treated with intravenous bisphosphonates compared with pretreatment values [61,62].…”
Section: Biphosphonatesmentioning
confidence: 95%
“…The treatment options with bisphosphonates and their potential side effects were discussed with the girl and her family as per our protocol. 11,17 After consenting, she received intravenous zoledronic acid 0.0125 mg/kg on day 1 and 0.025 mg/kg on day 2 followed 3 months later with 2 days of 0.025 mg/kg, after which she has been followed for 1 year. She has had no adverse effects to zoledronic acid therapy.…”
Section: Casementioning
confidence: 99%
“…The treatment option with bisphosphonate and its potential side effects were discussed with the child and his family as per our protocol. 11,17 After consenting, he received pamidronate 0.75 mg/kg intravenously once daily on 2 successive days (described as a cycle). 17 He received another cycle 3 months and a year later.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…More specifi cally, pamidronate treatment has resulted in improved bone mineral density (6,7) and decreased fracture rate (8,9) and some of this effect appears to persist over time (10) . Pamidronate has a respectable safety record, with asymptomatic hypocalcemia being the most common side effect.…”
Section: Introductionmentioning
confidence: 99%